2015
DOI: 10.1177/0022042615604013
|View full text |Cite
|
Sign up to set email alerts
|

Change in Adolescents’ Alcohol-Use Patterns, From Non-Drinking to Non-Heavy Drinking or Heavy Drinking

Abstract: This study examined risk and protective factors at work when adolescents change from a nondrinking alcohol-use pattern to either non-heavy drinking or heavy drinking. Using a sample of 1,725 non-drinkers extracted from the National Longitudinal Study of Adolescent to Adult Health, we conducted multinomial logistic regression and found that likelihood of change from non-drinking to non-heavy drinking was associated positively with safe neighborhood, female, peers' drinking, emotional maltreatment, and delinquen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…This is due to NA and PA exhibiting a linear negative and positive association, respectively, with non-heavy alcohol use, though they are quadratically related to BD. Indeed, studies suggest that NA increases the risk for BD more so than for non-heavy alcohol use and that individuals who experience more NA are more likely to start BD (Cheng & Lo, 2015;Stene-Larsen et al, 2013). Second, it seems that non-heavy alcohol use could play a larger role in affect regulation in daily life than BD.…”
Section: Differences Between Non-heavy Alcohol Use or Binge Drinkingmentioning
confidence: 99%
“…This is due to NA and PA exhibiting a linear negative and positive association, respectively, with non-heavy alcohol use, though they are quadratically related to BD. Indeed, studies suggest that NA increases the risk for BD more so than for non-heavy alcohol use and that individuals who experience more NA are more likely to start BD (Cheng & Lo, 2015;Stene-Larsen et al, 2013). Second, it seems that non-heavy alcohol use could play a larger role in affect regulation in daily life than BD.…”
Section: Differences Between Non-heavy Alcohol Use or Binge Drinkingmentioning
confidence: 99%
“…The data have insufficient information on friends' substance use, for example, even though this is associated with most forms of adolescent substance use (Henneberger, Mushonga & Preston, 2021). A feasible pathway is from low-quality relations with parents to substance using peers, which in turn affects the likelihood of problem substance use (Cheng & Lo, 2015). Associating with substance using peers might also affect relations with parents and religious beliefs and practices (Hoffmann, 2014).…”
Section: Limitationsmentioning
confidence: 99%
“…Although the majority of youth who start drinking alcohol do not become problem drinkers, binge drinkers reported the highest rates of problem behavior, drug use, and poor grades (Tucker et al, 2003). Cheng and Lo (2015) found that the likelihood of changing from non-drinking to non-heavy drinking was positively associated with variables such a peers' drinking, emotional maltreatment, and delinquent behaviors.…”
Section: Introductionmentioning
confidence: 95%
“…The importance of how environmental and ecological contexts shape youth behaviors and outcomes have long been discussed in the literature (Ennett et al, 1997). Family, neighborhood, and school ecologies all can impact youth outcomes (e.g., Cheng & Lo, 2010, 2015; Ennett et al, 1997). Given the amount of time youth typically spend at school, the school context in particular could significantly shape the correlates, predictors, and outcomes commonly reported in the practice and research literature (Bacio et al, 2015).…”
Section: Introductionmentioning
confidence: 99%